Prevalence of Hematotoxic Effect of Intravenous Chemotherapy among Retinoblastoma Population in Tertiary Hospital in Bandung, Indonesia - Jennifer Hadiman; Susi Susanah; Adhi Kristianto Sugianli (International Journal of Integrated Health Sciences, 2019)
Objective: To observe the prevalence of hematotoxic effect in retinoblastoma patients who were given intravenous chemotherapy with vincristine, etoposide, and carboplatin (VEC) regimen. Retinoblastoma is the second most common cancer in children in Indonesia. Standard chemotherapy agents used in retinoblastoma treatment is VEC given in 7 cycles intravenously. The most common side effect of VEC regimen is hematotoxic effect which might lead to chemotherapy failure.Methods: This study used descriptive method with cross sectional study design. Data were collected from medical records of retinoblastoma patients in Dr. Hasan Sadikin General Hospital Bandung, Indonesia, from 2014 until 2016 using total sampling technique.Results: Forty-six patients were included in this study. Of those subjects, 36 (78.3%) patients experienced hematotoxic effect. The most common hematotoxic effect occurred were anemia and neutropenia, that occurred in 32 (69.6%) and 18 (39.1%) patients, respectively. The most common hematotoxic effect severity occurred were grade 1 anemia, grade 1 leukopenia, grade 1 neutropenia, and grade 3 thrombocytopenia. Percentage of patients experienced anemia tended to increase until the 7th cycle. Seven (15.2%) patients had anemia prior to chemotherapy administration.Conclusion: The majority (78.3%) of the patients experienced hematotoxic effect on intravenous chemotherapy administration with VEC regimen. Anemia was the most common hematotoxic effect occurred.Keywords: Hematotoxic effect, intravenous chemotherapy, retinoblastoma